A Study to Assess the Knowledge on First-Aid Management of Burns Among Adults Living in Selected Areas at Honavar, Uttara Kannada with A View to Organize a Demonstration Programme - Rakesh Gomes; Ananya John; Dona Saji; Netravati More; Anjana Baby; Deepika.S; Amala Mathew; Mamata Kumari; Tismi.K.Tomy (International Journal of Emergency and Trauma Nursing and Practices, 2024)
Title: A Study to Evaluate the Awareness of First-Aid Treatment for Burns among Adults Residing in Specific Areas of Honnavar, Uttara Kannada, Aimed at Organizing a Demonstration Program. Aim: To assess the knowledge on first-aid management of burns and conduct a demonstration program on domestic fire accident. Methodology: A one group pre-test only design was adopted. A total of 100 participants who met the inclusion criteria were chosen through a random convenience sampling method. Data was gathered using a self-designed questionnaire focused on first-aid management for burns. The Chi-square test was applied to assess the relationship between participants' knowledge and their demographic characteristics. Results: Of the 100 samples 15(15%) had poor knowledge, 55(55%) had average knowledge, 24(24%) had good knowledge and 6(6%) had excellent knowledge. Conclusion: The findings reveal that, majority of the subjects had average knowledge and few had poor knowledge as well. As limited research has been conducted on this topic in India, nurse researchers can explore further studies on the same subject
Keywords: Knowledge; demonstration programme; first- aid management of burns